2020
DOI: 10.25304/rlt.v28.2323
|View full text |Cite
|
Sign up to set email alerts
|

Have a question? Just ask it: using an anonymous mobile discussion platform for student engagement and peer interaction to support large group teaching

Abstract: This article analyses the pilot of an anonymous question and answer mobile application with a large cohort of undergraduate students (460) enrolled on an Operations Strategy Management module. The mobile application allowed students to pose anonymous questions to both peers and staff, create replies and vote on questions posted by other users. The aim of the pilot was to evaluate how this application could be used to enhance communication, engagement and student learning both inside and outside of class time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Several of these tools have been developed (e.g., Backstage , [ 36 ]) recently, but in general they allow students to contribute to course dialogue through an app on their devices, with their input projected—typically anonymously—on a shared screen. Some investigators have indicated that, in line with our initial findings, these backchannels can increase the number—and possibly the diversity—of students engaging in class [ 35 , 37 39 ]. However, research on the utility and impact of these backchannels is still emerging.…”
Section: Resultssupporting
confidence: 70%
“…Several of these tools have been developed (e.g., Backstage , [ 36 ]) recently, but in general they allow students to contribute to course dialogue through an app on their devices, with their input projected—typically anonymously—on a shared screen. Some investigators have indicated that, in line with our initial findings, these backchannels can increase the number—and possibly the diversity—of students engaging in class [ 35 , 37 39 ]. However, research on the utility and impact of these backchannels is still emerging.…”
Section: Resultssupporting
confidence: 70%
“…Virtual mentoring is quite effective and also allows students anonymity when asking questions, which can encourage quiet students. 4,14…”
Section: Novel Initiativementioning
confidence: 99%